Income Inequality in Peru According to 1876 Census - Castillo Vera, Paula (2017)
Inequality is a social phenomenon that exists across all nations; it is a condition which means that not everyone enjoys the same access to resources of all kinds and to certain positions that society values. Despite its importance, in Peru, the analysis of different approaches to inequality was not taken up until the 20th century, since it was only then that data began to be prepared to enable its study. Because detailed analyses of inequality did not exist before the 20th century, the objective of this study is to estimate income inequality in Peru at the end of the 19th century on the basis of the 1876 census, the first population and housing census of the Republican era. This census is considered to be particularly important for its utilization of modern techniques to enumerate the inhabitants of the day.